Maternal gut microbiota and placenta-derived tissues microbes are important for initial gut microbial colonization in infants - Zhang, Ziyi; Jia, Longlong; Liu, Bin; Liu, Yanpin; Zhao, Junying; Wang, Yaling; Zhang, Minghui; Qiao, Weicang; Yang, Baoyu; Luo, Lingling; Chen, Lijun (Frontiers in Microbiology, 2025)
BackgroundEarly infant gut microbiota colonization, influenced by various factors, significantly affects future growth and development. However, results related to how the initial microbial ecology is established in the infant gut remain inconsistent.ResultsIn this study, we collected maternal and infant feces, vaginal secretions, placental tissues, breast milk, amniotic membrane tissues, umbilical cord blood, and breast skin for homology comparisons and for exploring the main sources of infant intestinal microbiota. Our results revealed that early infant gut microbiota originated mainly from the vertical transmission of maternal microbiota, and that vaginal microbiota did not affect infant gut microbiota colonization. Microbiota was detected in the placenta, supporting the idea that the uterus is not sterile. Moreover, we verified microbial composition-related similarities in the amniotic tissues and umbilical cord blood, further validating our hypothesis that gut microbiota in the early stages of infancy are mainly vertically transmitted from the mother and placenta-derived tissues also play a significant role in the formation of the infant’s initial gut microbiota. Notably, none of the hereby-mentioned influences (i.e., gender, delivery mode, feeding mode, and Hepatitis B virus) affected significantly infant gut microbiota colonization.ConclusionThis study demonstrated that infant intestinal microbiota resulted from microbiotic co-provision from multiple maternal sites. In addition to the maternal gut microbiota, the placenta-derived tissues is the relevant contributor to initial infant gut microbiota, providing strong evidence for the source colonization of the infant gut microbiota.